Parent and child interactions with two contrasting anti-obesity advertising campaigns: A qualitative analysis - Thomas, S.; Olds, T.; Pettigrew, Simone; Yeatman, H.; Hyde, J.; Dragovic, C. (BioMed Central Ltd, 2014)
Background: Social marketing has been proposed as a framework that may be effectively used to encourage behaviour change relating to obesity. Social advertising (or mass media campaigning) is the most commonly used social marketing strategy to address the issue of obesity. While social advertising has the potential to effectively communicate information about obesity, some argue that the current framing and delivery of these campaigns are ineffective, and may cause more harm than good. Methods: We used a qualitative advertising reception study. 150 family groups (comprised of 159 parents and 184 children) were shown two Australian government anti-obesity advertisements: Measure Up (focused on problems associated with obesity) and Swap It (focused on solutions for obesity). Families were engaged in a discussion about the visual appeals, verbal messages and their perceptions about the impact of the advertisements on behavioural change. Open coding techniques and a constant comparative method of analysis was used to interpret the data.Results: Many parents had strong personal resonance with the visual imagery within the campaigns. While Swap It had strong ‘likeability’ with children, many children believed that the messages about overweight and obesity were less personally relevant because they did not perceive themselves to be overweight. The content and delivery style of the verbal messages (the serious risk focused message in Measure Up compared to the upbeat, fun practical message in Swap It) influenced how different audiences (parents and children) interpreted the information that was presented. Parents assimilated practical and instructive messages, while children assimilated messages about weight loss and weight gain. Parents and children recognised that the campaigns were asking individuals to take personal responsibility for their weight status, and were at times critical that the campaigns did not tackle the broader issues associated with the causes and consequences of obesity. The lack of practical tools to encourage behavioural change was a key barrier for obese parents. Conclusions: Well-funded, targeted social marketing campaigns will play an important role in the prevention and management of obesity. It is important that these campaigns are comprehensively evaluated and are backed up with structural supports to enable and encourage population subgroups to act upon messages.